Slow Elevation in Protein C Activity without a PROC Mutation in a Neonate with Intracranial Hemorrhage - Erika Uehara; Hiro Nakao; Yusuke Tsumura; Hisaya Nakadate; Shoichiro Amari; Hideshi Fujinaga; Yoshiyuki Tsutsumi; Dongchon Kang; Shouichi Ohga; Akira Ishiguro (Thieme Medical Publishers, Inc., 2018)
Severe protein C (PC) deficiency leads to purpura fulminans and stroke in newborns. However, the clinical impact of plasma PC activity on the development of neonatal cerebral disease remains elusive. We report a case of hemorrhagic stroke associated with neonatal asphyxia and severe PC deficiency. Plasma PC and protein S activity 7 days after birth was 12% and 43%, respectively. No PROC mutation was found. PC levels did not exceed 20% until 2 months of age, even in the absence of consumption coagulopathy or vitamin K deficiency. Neither thromboembolic nor hemorrhagic events occurred during the infusion of activated PC concentrate (twice weekly, up to 68 days after birth). The PC activity levels gradually increased to the standard value for age by 9 months of age. The present case showed that neonatal PC deficiency without a PROC mutation caused an intracranial hemorrhage before a slow increase in PC activity.